Complex neural representation of odor information in the olfactory bulb - Li, Anan (Acta Physiol (Oxf), 2019)
The most important task of the olfactory system is to generate a precise representation of odor information under different brain and behavioral states. As the first processing stage in the olfactory system and a crucial hub, the olfactory bulb plays a key role in the neural representation of odors, encoding odor identity, intensity, and timing. Although the neural circuits and coding strategies used by the olfactory bulb for odor representation were initially identified in anesthetized animals, a large number of recent studies focused on neural representation of odorants in the olfactory bulb in awake behaving animals. In this review, we discuss these recent findings, covering (1) the neural circuits for odor representation both within the olfactory bulb and functional connections between the olfactory bulb and higher order processing centers; (2) how related factors such as sniffing affect and shape the representation; (3) how the representation changes under different states; and (4) recent progress on the processing of temporal aspects of odor presentation in awake, behaving. We highlight discussion of the current views and emerging proposals on the neural representation of odorants in the olfactory bulb.